2020
DOI: 10.11144/javeriana.sc25-3.coar
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of antibiotic-resistant Escherichia coli associated with urinary tract infections in Southern Colombia

Abstract: Bacterial resistance to antibiotics is one of the largest medical concerns worldwide.One of the bacteria of critical priority is E. coli, since it presents different resistance mechanisms and some of its strains have evolved resistance to beta-lactam antibiotics. We characterized 32 antibiotic resistant bacterial isolates from confirmed cases of urinary tract infections from an array of patients in Nariño, southern Colombia. Macro and microscopic descriptions of the 32 clinical isolates were conducted. Resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…However, a study conducted in Mozambique using ERIC-PCR analysis revealed that despite evidence of high genetic diversity among E. coli isolates, there was a predominance of few clones adapted to the hospital environment, what would they probably be HiRCs (17). Similar findings were reported in hospitals in Ethiopia (25) and Colombia (64). Analysis by pulsed field gel electrophoresis (PFGE, technique used to produce a DNA fingerprint for a bacterial isolate) also supports these findings: among the great diversity of pulse types (ST), ST405 and ST1284 circulate mainly in hospitals in Lebanon (38), while ST131 in Bangladesh (35) and USA (89,100).…”
Section: Genetic Diversity Of Antibiotic Resistant Isolatessupporting
confidence: 55%
See 2 more Smart Citations
“…However, a study conducted in Mozambique using ERIC-PCR analysis revealed that despite evidence of high genetic diversity among E. coli isolates, there was a predominance of few clones adapted to the hospital environment, what would they probably be HiRCs (17). Similar findings were reported in hospitals in Ethiopia (25) and Colombia (64). Analysis by pulsed field gel electrophoresis (PFGE, technique used to produce a DNA fingerprint for a bacterial isolate) also supports these findings: among the great diversity of pulse types (ST), ST405 and ST1284 circulate mainly in hospitals in Lebanon (38), while ST131 in Bangladesh (35) and USA (89,100).…”
Section: Genetic Diversity Of Antibiotic Resistant Isolatessupporting
confidence: 55%
“…No most of them presented often resistance to fluoroquinolones, ampicillin, co-trimoxazole and cephalosporins (3,4,11,17,21,26,33,39,54,62,64,73,85,110). Moolchandani et al, recommends not using these antibiotics for empirical therapy of urinary tract infections acquired in ICUs in South India; instead, they suggest considering imipenem, pipericillin-tazobactam, amikacin, and nitrofurantoin for initial therapy with prompt de-escalation after culture and sensitivity results are received (3).…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The genomic DNA of colistin-resistant isolates was subjected to PCR for the detection of antimicrobial-resistant genes against specific antibiotics, including β-lactamase genes ( bla CTX-M , bla TEM , and bla SHV ), Aminoglycosides (Gentamycin, aac-3-IV , Streptomycin, aadA1 ), Fluoroquinolones (Ciprofloxacin, aac ( 6- ) -lb ), Tetracyclines (Tetracycline, tetA ), Chloramphenicol ( catA1 and floR ) and Fosfomycins (Fosfomycin, fosA ) by previously designed oligonucleotide primers and protocols ( Tables S1 and S2 ) [ 36 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Se determinó mediante la técnica de Bauer Kirby el perfil de resistencia de las bacterias patógenas E. coli y S. aureus aisladas de muestras hospitalarias y conservadas en el Banco de Células Primarias del Laboratorio de Procesos Microbianos de la Universidad de Nariño se determinó mediante la técnica de Bauer Kirby (19,20) . Los antibióticos usados fueron: (P) penicilina, (SAM) ampicilina (10g), (AMC) amoxicilina (30g), (CTX) cefotoxima (30g), (STX) trimetroprim-sulfametoxazol (25g), (CN) gentamicina (10g), (ATM) aztreonam, (CIP) ciprofloxacina (5g), (IPM) imipenem, (AK) amikacina (30g), (S) estreptomicina (10g) y (EM) eritromicina (30g) (OXOID).…”
Section: Perfil De Resistencia a Antibióticos De Las Bacterias Patógenasunclassified